The industrial colony of Belišće factory facilities, infrastructure, and transportation on Gutmann's estate - Volner, Hrvoje (2020)
Gutmann’s company became involved with industrial wood processing in the mid-19th century, due to the demand for railroad ties for the purpose of building a railway network in the post-revolutionary Habsburg Monarchy. In the wood processing business, the company would hold its steady place word for almost a century, until the Ustasha regime and then the Communist government put an end to its tradition. Its fate was finally sealed in 1946 by the District People’s Court in Zagreb. Belišće was founded in 1884 and within a few years acquired the form of an industrial settlement with factory facilities, warehouses, administrative buildings, cultural centres, and typical apartment buildings. By the end of the interwar period, Belišće had the population of a smaller urban settlement, with a post office serving a number of surrounding villages, factories, a port on the river Drava, and a railway network as a starting point in connecting Slavonia-Podravina with the foot of Mount Papuk in Voćin.Gutmann’s industrial plants, infrastructure and workers were the backbone of a successful family business, which consequently built the township of Belišće.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 105-107.
Summary.
Keywords: Industrija -- Urbanizacija -- Željeznica -- Radnici -- Povijest; Belišće